Pengaruh Latihan Servis Jarak Bertahap Menggunakan Bola Plastik dan Bola Tenis Terhadap Ketepatan Servis Atas Bola Voli Putri Yunior Provos Pemalang - Muhammad Rafi Faishal Faishal; Agus Wiyanto; Danang Aji Setiawan (YLPK Mahardhika, 2022)
The background of this research is that participants often do not enter when serving on the opponent's court, lack of accuracy in hitting the ball when serving over, low level of service accuracy. The purpose of this study is to examine how effective concentration and eye-hand coordination exercises using plastic balls and tennis balls are in training the accuracy of serving on volleyball for Putri Junior Provos Pemalang.The discussion of the results of the study was carried out using a quantitative approach to the experimental two groups pretest-posttest design. In this design the sample will be divided into two groups according to the ranking of the initial test from the lowest to the highest by zig-zag or Matched Subject Ordinal Pairing (AB-BA) so that both groups have equal abilities (equivalent).The results showed that 1) There was a significant effect of the implementation of the gradual distance service exercise using a plastic ball on the accuracy of serving on the Pemalang Provos Junior Women's volleyball. This can be proven from the tcount of the experimental group 1 (7.839) with a significance of 0.001 (0.001 <0.05); 2) There is a significant effect of the implementation of the gradual distance service exercise using a tennis ball on the accuracy of serving on the Pemalang Provos Junior Women's volleyball. This can be proven from the tcount of the experimental group 2 (10.633) with a significance of 0.000 (0.000<0.005); 3) Based on the results of the N-Gain Score test, it shows that the average N-gain score for experimental group 1 (plastic ball) is 5.7138 or 25.7%. With a minimum N-gain score of 3.23% and a maximum of 7.9%. Meanwhile, the average N-gain score for the experimental group 2 (tennis ball) was 6.8220 or 6.8%. With a minimum N-gain score of 5.38% and a maximum of 8.8%.The conclusion of the study is that the application of training using tennis balls in a gradual distance service exercise is more effective than using a plastic ball on the accuracy of serving on women's volleyball. My suggestion is that the media in this exercise can be used in the Putri Junior Provos volleyball club in Pemalang.